Sex Partner Meeting Places Over Time Among Newly HIV-Diagnosed Men Who Have Sex With Men in Baltimore, Maryland. Issue 10 (October 2015) - Jennings, Jacky M.; Reilly, Meredith L.; Perin, Jamie; Schumacher, Christina; Sharma, Megha; Safi, Amelia Greiner; Fields, Errol L.; Muvva, Ravikiran; Nganga-Good, Carolyn; Chaulk, Patrick
<x xml:space="preserve">Abstract</x> Background Sex partner meeting places may be important locales to access men who have sex with men (MSM) and implement targeted HIV control strategies. These locales may change over time, but temporal evaluations have not been performed. Methods The objectives of this study were to describe the frequency of report of MSM sex partner meeting places over time and to compare frequently reported meeting places in the past 5 years and past year among newly HIV-diagnosed MSM in Baltimore City, Maryland. Public health HIV surveillance data including partner services information were obtained for this study from the Baltimore City Health Department from May 2009 to June 2014. Results A total of 869 sex partner meeting places were reported, including 306 unique places. Bars/clubs (31%) and Internet-based sites (38%) were the most frequently reported meeting place types. Over the 5-year period, the percentage of bars/clubs decreased over time and the percentage of Internet-based sites increased over time. Among bars/clubs, 4 of 5 of those most frequently reported in the past 5 years were also most frequently reported in the most recent year. Among Internet-based sites, 3 of 5 of those most frequently reported in the past 5 years were also in the top 5 most frequently reported in the past year. Conclusion This study provides a richer understanding of sex partner meeting places reported by MSM over time and information to health departments on types of places to access a population at high risk for HIV transmission.